Preeclampsia Induced Liver Dysfunction Complicated by Disseminated Intravascular Coagulopathy and Placental Abruption: A Case Report and Review of the Literature - Jordan Myers; Gary Wu; Robert E. Shapiro; Manuel C. Vallejo (Case Reports in Anesthesiology)
A 33-year-old primigravida at 32-week gestation was admitted to labor and delivery complaining of severe right upper quadrant pain and worsening coagulopathy. We report the anesthetic and obstetrical management of a complex case of a parturient with a mixed picture of hemolysis, elevated liver enzymes and low platelets who was delivered under general anesthesia further complicated by Disseminated Intravascular Coagulopathy (DIC) and placental abruption.